Development of electrospun chitosan/polyvinyl alcohol membranes with antibacterial properties for enhanced open wound healing - Luu Ngoc Hanh Cao; Thi Bich Thuyen Nguyen; Tuong Vy Nguyen; Truong Ngoc Mai Ngo; Thi Hang Phung; Thanh Ty Nguyen (CTU Journal of Innovation and Sustainable Development)
This work focuses on using the electrospinning process to fabricate a microfiber membrane for wound healing by combination of chitosan (CS) and polyvinyl alcohol (PVA). The impacts of several parameters on fiber morphology and antibacterial capabilities, such as PVA concentration, CS/PVA ratio, applied voltage, injection distance, and solution injection speed, were investigated. The ideal parameters for the electrospinning process were identified as follows: PVA concentration of 15%, CS/PVA ratio of 3/7, collecting distance of 10 cm, voltage of 11 kV, and flow rate of 0.085 mL/h. Scanning electron microscopy verified the fiber structure was homogeneous and particle-free, with an average diameter of 457 ± 111 nm. The CS/PVA microfiber membrane demonstrated strong antibacterial action against E. coli and L. monocytogenes strains. After 12 days, in-vivo tests demonstrated that the wound-healing capacity of the CS/PVA microfiber membrane was quicker than that of a self-healed wound sample. These results demonstrate the effective creation of CS/PVA microfibers for wound healing applications.